Pengaruh Edukasi terhadap Kepatuhan Minum Obat Pasien Hipertensi : A Literature Review - Sri Nabawiyati Nurul Makiyah; Irwan Embang Walanda (Citra Delima Scientific journal of Citra Internasional Institute, 2021)
Education was a form of independent nursing action to help hypertension sufferers, both individuals, groups, and communities in overcoming their health problems through learning activities, in which nurses are as nurse educators. Objective to conducting a literature review of articles that examine the effect of education on medication adherence for hypertensive patients. Methods Using a database with EBSCO search, Google Scholar, Scien Diract, Pubmed published in 204-2019. Result Respondents were used aged 30-70 years in hypertensive patients. This literature review shows that there is a significant effect of giving education and counseling to medication adherence in hypertensive patients (P = 0.00). There was an influence of education and counseling on medication adherence in hypertensive patients.